Overview of cultivated and wild species of the Oleaceae family (Fabaceae s.l.) in the Emirate of Fujairah (United Arab Emirates) - Byalt Vyacheslav Vyacheslavovich; Korshunov Mikhail Vladimirovich (Hortus Botanicus)
The article provides an overview of the family Oleaceae in the flora of the emirate of Fujairah, located in the mountainous northeastern part of the United Arab Emirates (UAE). We studied the flora of the emirate for 6 years, from 2017 to 2022. As a result of field research, examination of irrigated gardens, public parks, urban plantings and plant nurseries, herbarium materials and literature data, a list of wild and cultivated plant species growing here was compiled. The article provides an annotated list of representatives of the Oleaceae (introduced and native), which we identified in the emirate of Fujairah, including both literature and herbarium data, and data from the authors based on the results of original surveys of the territory of the emirate as of the spring of 2024. Genera and species are arranged in alphabetical order. The family list within the administrative boundaries of Fujairah, both for natural habitats and for public places: city gardens and parks, boulevards and embankments, squares, streets and local areas is given. Data on species found in plant nurseries were taken into account. The list contains 12 species from 3 genera. Native and alien, cultivated (ergasiophytes) and wild from cultivation (ergasiophygophytes – ephemerophytes, colonophytes and epoecophytes): Olea africana Mill. (O. europaea subsp. cuspidata (Wall. ex G. Don) Cifferi) – native species; Jasminum azoricum Vahl, J. sambac L. and Olea europaea L. s. str. is listed as a new alien alien species for Fujairah. For the first time, they are recorded as alien wild or introduced species for the UAE andArabia as a whole.